A survey-based cross-sectional study of doctors’ expectations and experiences of non-technical skills for out of hours work - Brown, Michael; Shaw, Dominick E.; Sharples, Sarah; Le Jeune, Ivan; Blakey, John (BMJ Publishing Group, 2015)
Objectives: The skill set required for junior doctors to work efficiently and safely Out of Hours (OoH) in hospitals has not been established. This is despite the OoH period representing 75% of the year and it being the time of highest mortality. We set out to explore the expectations of medical students and experiences of junior doctors of the non-technical skills needed to work OoH.